THE PROLIFERATION OF NUCLEAR WEAPONS IN NORTH KOREA: INTERNATIONAL LAW PERSPECTIVE - Yordan Gunawan; Rima Ayu Andriana (STIH Putri Maharaja, 2019)
The proliferation issue of nuclear weapons in North Korea is becoming a more serious problem to the international community. North Korea has been manufacturing and developing nuclear weapons technology, which receives many critics by the international community expressing that North Korea is being non-compliance with the Treaty on the Non-Proliferation of Nuclear Weapons (NPT) 1968. The criticism emerged following the North Korea withdrawal from the NPT 1968. Its withdrawal reasoning seems very hard to be justified after series of non-compliance behavior conducted by North Korea and the legitimacy of its withdrawal is being debated. By using normative legal research, the research aims to determine the status of North Korea upon its withdrawal from the NPT 1968 based on the withdrawal procedure that is required in the Article X of the NPT 1968. The result shows that North Korea is still a member and it is bound by the obligations contained in the Treaty and to make progress on a complete nuclear disarmament regime.